PCR and direct fluorescent-antibody staining confirm Chlamydia trachomatis antigens in swabs and urine below the detection threshold of Chlamydiazyme enzyme immunoassay. - Krepel, J (1995)
In order to test the hypothesis that specimens blocking with a neutralizing reagent below the cutoff of the Chlamydiazyme enzyme immunoassay represent infected patients, we used direct fluorescent-antibody staining for elementary bodies (EBs) and PCR to confirm results for cervical swabs collected from 55,963 women and urethral swabs or first-void urine (FVU) samples collected from 5,781 men attending physicians' offices in the Toronto, Canada, area. Within a grey zone arbitrarily selected to represent values up to 40% below the positive threshold of the test run, 134 cervical swabs, 44 urethral swabs, and 39 FVU specimens exhibited a blocking response ( > 50% reduction in signal). Three or more EBs were observed in each of 98 cervical swabs (73.1%), 38 urethral swabs (86.4%), and 21 FVU specimens (53.8%). Of the 36 cervical swabs with fewer than three EBs, 33 were PCR positive; the positive PCR results for male specimens were 6 of 6 urethral swabs and 17 of 18 FVU samples. Application of the blocking test to specimens negative in the Chlamydiazyme enzyme immunoassay but having optical densities within 40% of the cutoff added 14.2% (217 of 1,531 specimens) more positive results to the survey. A total of 213 of 217 samples (98.2%) were reconfirmed as having EBs or DNA.